(untitled) (Web of Teachers: Inderscience Research, 2025)
The article presents a theoretical analysis of habituality in suprasentential units. Special attention is given to the role of habituality as a linguistic phenomenon that reflects regularity and recurrence of actions in language, as well as its manifestation in more complex syntactic structures than simple sentences. The author analyzes the use of various grammatical means—such as verb forms, temporal adverbs, complex sentences, and modal constructions—for expressing habituality in texts. The paper describes the influence of habituality on textual organization and its role in creating logical sequence and cohesion within the text. The study highlights the importance of habituality as a key element for deeper understanding of the temporal structure of language and its capacity to describe regular and recurring actions.